THE STUDY OF LIFE INSURANCE CLAIMS APPLICATION SYSTEM-TAKING B COMPANY AS EXAMPLE - Lin, Linda Lin-Chin; Kuo, Hsing-Yi; Lin, Chin-Chiuan (Graduate Program of Universitas Tarumanagara, 2025)
In the era of Big Data, data obtained cannot be responded to only by traditional storage devices. Relatively low-cost and flexible cloud platforms can be used to meet the demand of insufficient database capacity. This is an important part of the current enterprise's deployment of digital transformation. However, no matter how technology evolves, huge data still needs to rely on manual processing and proofreading before it can be stored in the cloud database for future re-application and sharing. A major challenge for an enterprise is whether the information technology tools configured by the enterprise can effectively store and retrieve data quickly and correctly through the cloud data sharing platform to meet its operational needs. If the enterprise can configure a set of corresponding information technology tools to increase the processing capacity of big data, it can naturally improve the internal efficiency of the enterprise, maximize its output value and gain market competitive advantage. In order to understand whether the claims application system currently configured by life insurance companies has sufficient cloud big data processing capabilities, whether it can improve the efficiency of internal operations of the enterprise, and whether its application can meet the needs of claims adjusters, etc., this study uses task-technology fit model (TTF) is used as the theoretical basis and computer self-efficacy is introduced as a pre-factor. The questionnaire statistics